ECTOPIC INNER FOVEAL LAYER CLASSIFICATION SCHEME PREDICTS VISUAL OUTCOMES AFTER EPIRETINAL MEMBRANE SURGERY. Issue 4 (April 2020) - González-Saldivar, Gerardo; Berger, Alan; Wong, David; Juncal, Verena; Chow, David R.
Abstract : Purpose: To evaluate the ectopic inner foveal layer (EIFL) staging scheme as a visual prognostic factor for patients undergoing epiretinal membrane (ERM) surgery. Methods: Retrospective study of 88 pseudophakic patients with diagnosis of idiopathic ERM who underwent ERM surgery with a minimum follow-up of 12 months. Preoperative and postoperative EIFL staging was correlated with the final best-corrected visual acuity (BCVA). As a secondary outcome, evaluation of the proportion of patients achieving final best-corrected visual acuity ≥20/40 in each stage was assessed. Results: Based on the EIFL staging scheme, of 88 pseudophakic eyes analyzed, 24 (27.4%) were diagnosed as Stage 2 ERM, 45 (51.1%) as Stage 3 ERM, and 19 (21.5%) as Stage 4 ERM preoperatively. At the final follow-up visit, 70.8% of eyes with Stage 2 showed an improvement in EIFL staging scheme, while 68% of eyes in Stage 3 and 4 remained the same. The final best-corrected visual acuity significantly improved with all EIFL stages ( P = <0.05). However, earlier stages were associated with better visual outcomes both preoperatively and postoperatively (Stage 2 > Stage 3 > Stage 4 P < 0.001). Final best-corrected visual acuity ≥20/40 was reached in 91.7% of eyes with Stage 2, 42.3% with Stage 3, and 5.2% with Stage 4. Conclusion: The EIFL staging scheme is an easy, fast, and reproducible method to evaluate visual prognosis with ERM surgery. Surgery on Stage 2 ERM results in significantly better visual outcomes and a greater chance of reversibility in anatomical changes. Abstract : Ectopic inner foveal layer classification scheme is an easy, fast, and reproducible method to evaluate visual prognosis of epiretinal membrane. Final best-corrected visual acuity was ≥20/40 in 91% of the eyes having surgery at Stage 2, and 70% of them improved to Stage 1. Ectopic inner foveal layer scheme should be part of the decision process for epiretinal membrane surgery.